2011
DOI: 10.1177/1352458511431072
|View full text |Cite
|
Sign up to set email alerts
|

Advanced magnetic resonance imaging of neuromyelitis optica: a multiparametric approach

Abstract: Our data disclosed occult structural damage in the brain of patients with NMO, predominantly involving regions connected with motor and visual systems. This damage seems to be the direct consequence of transsynaptic degeneration triggered by lesions of the optic nerve and spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 29 publications
9
65
2
Order By: Relevance
“…4) [84]. Another group consistently showed that DTI OR FA reductions were exclusively confined to visual pathway structures in NMOSD [81]. This notion is fostered by other study results reporting evidence on OR DTI value alterations only in regions of corticospinal or visual pathways [76,100,101].…”
Section: Visual Pathway Dti In Nmosd Optic Nerve Dti In Nmosdsupporting
confidence: 55%
See 1 more Smart Citation
“…4) [84]. Another group consistently showed that DTI OR FA reductions were exclusively confined to visual pathway structures in NMOSD [81]. This notion is fostered by other study results reporting evidence on OR DTI value alterations only in regions of corticospinal or visual pathways [76,100,101].…”
Section: Visual Pathway Dti In Nmosd Optic Nerve Dti In Nmosdsupporting
confidence: 55%
“…fractional anisotropy) [80] has been sporadically reported to be present in the visual system of NMOSD patients indicating demyelination processes to occur within the OR. Up to now, there were no consistent reports on AD changes as a correlate of potential axonal damage within the OR throughout the literature [80,81]. Collectively, these findings are highly indicative of transsynaptic anterograde degeneration spreading from the optic nerves to the OR in NMOSD.…”
Section: Visual Pathway Dti In Nmosd Optic Nerve Dti In Nmosdmentioning
confidence: 76%
“…70 Regional voxelbased morphometry analysis in the same cohort identified possible volume loss clustered in the optic radiations and corpus callosum. Finally, the metabolic pattern of normal-appearing white matter in NMO/NMO spectrum disorder, as assessed by multivoxel chemical shift imaging at 1.5T 56,63 and 3T 62 with 1 H-MR spectroscopy, is identical to that in controls. Taken together, these studies indicate subtle and, with the possible exception of the corpus callosum, selective structural alterations in the optic and motor pathways in the brain, implicating trans-synaptic axonal degeneration secondary to destructive lesions in the optic nerves and spinal cord, respectively.…”
Section: Normal-appearing White Mattermentioning
confidence: 94%
“…and volume of gray matter in the motor and visual cortices and regions associated with executive and language functions in patients with NMO (n ϭ 8) versus healthy controls (n ϭ 7) by using a similar voxel-based morphometry method (Fig 6A, -B). MT imaging has been explored in NMO, thus far with discrepant results: Rocca et al 57 observed a reduced MT ratio in normal-appearing gray matter in 10 patients with NMO, suggesting occult gray matter damage, while Pichiecchio et al 56 observed no differences in either the cortical or deep gray matter MT ratio between patients (n ϭ 8) and healthy controls (n ϭ 7). Finally, while iron deposition in the deep gray matter structures is described in MS 71 and may contribute to disease progression, 72 Chen et al 64 found no evidence of abnormal iron deposition in the putamen, globus pallidus, caudate nucleus, thalamus, substantia nigra, red nucleus, or dentate nucleus by using quantitative 3D-enhanced susceptibilityweighted angiography in 42 patients with NMO compared with healthy controls.…”
Section: Cortical and Deep Gray Matter Pathologymentioning
confidence: 95%
See 1 more Smart Citation